The spittlebug Mahanarva fimbriolata (Stål) produces foam as a thermoregulatory and defensive strategy - Tonelli, Mateus (2019)
Insects of the family Cercopidae are easily identified by the spit-like foam that they produce to surround themselves during the nymphal stage. Known as spittlebugs, these insects can be observed developing in a wide range of host plants. Among the functions attributed to the foam, there are the protection of nymphs against high temperatures, desiccation and natural enemies. However, experimental evidence to confirm these hypotheses are sparse. Mahanarva fimbriolata is an economically important spittlebug in Brazilian sugarcane crops, especially after the harvest with burning had been prohibited. The nymphs of M. fimbriolata develop on the soil surface or below ground where they suck the xylem content of exposed sugarcane roots, blocking the water and nutrients transport, eventually causing physiological disorder. In this thesis, it was evaluated the importance of foam for the thermoregulation of M. fimbriolata nymphs, its bacterial microbiome and the protective action against predators. The thesis was divided into four chapters. The Chapter 1 presented an introduction to the bioecological aspects of M. fimbriolata and the possible role of foam produced by the nymphs, which was explored in details along the other chapters. The Chapter 2 examined the importance of foam and its chemical compounds in the thermoregulation of nymphs. The Chapter 3 explored the diversity and composition of bacterial community present in the foam, in the gut of nymphs, and in the soil close to the foam. The Chapter 4 investigated whether the foam acts in protecting the nymphs against the predatory ants Solenopsis invicta, and its topical irritancy to the cockroaches Periplaneta americana. It was demonstrated that the foam produced by M. fimbriolata: (i) serves as an important thermal microhabitat, maintaining the temperature close to the ideal for the nymphs development; (ii) harbor a diversity of bacteria previously reported as protective symbionts of insects, which are probably originated from the nymphs\'s gut; and (iii) is a repellent to predators and topical irritant to another arthropod (roaches). Taken together, the foam produced by M. fimbriolata is a thermoregulatory and defensive strategy to the nymphs. In addition, this thesis serves as a background for future research that aims to investigate the importance of foam for the growth and development of spittlebugs.